Enhanced wind mixing and deepened mixed layer in the Pacific Arctic shelf seas with low summer sea ice - Yuanqi Wang; Zhixuan Feng; Peigen Lin; Hongjun Song; Jicai Zhang; Hui Wu; Haiyan Jin; Jianfang Chen; Di Qi; Jacqueline M. Grebmeier (Nature Communications)
Abstract The Arctic Ocean has experienced significant sea ice loss over recent decades, shifting towards a thinner and more mobile seasonal ice regime. However, the impacts of these transformations on the upper ocean dynamics of the biologically productive Pacific Arctic continental shelves remain underexplored. Here, we quantified the summer upper mixed layer depth and analyzed its interannual to decadal evolution with sea ice and atmospheric forcing, using hydrographic observations and model reanalysis from 1996 to 2021. Before 2006, a shoaling summer mixed layer was associated with sea ice loss and surface warming. After 2007, however, the upper mixed layer reversed to a generally deepening trend due to markedly lengthened open water duration, enhanced wind-induced mixing, and reduced ice meltwater input. Our findings reveal a shift in the primary drivers of upper ocean dynamics, with surface buoyancy flux dominant initially, followed by a shift to wind forcing despite continued sea ice decline. These changes in upper ocean structure and forcing mechanisms may have substantial implications for the marine ecosystem, potentially contributing to unusual fall phytoplankton blooms and intensified ocean acidification observed in the past decade.